Peran Pendidikan Agama Kristen Melawan Diskriminasi Di Masyarakat Majemuk Indonesia - Barus, Rona Ganta; Rahayu, Khatrina Rintis Lintang; Tandana, Ester; Liantoro, Liantoro; Darmadi, Darmadi (Indonesian Journal of Religious, 2022)
This article examines the role of Christian religious education in combating discrimination within a diverse Indonesian society. It explores the challenges posed by discrimination based on factors such as ethnicity, religion, and socio-economic status, and highlights the potential of Christian religious education to promote tolerance, respect, and inclusivity. The study investigates the principles and teachings of Christianity that emphasize equality, justice, and love for one's neighbor. It analyzes how Christian religious education can contribute to dismantling discriminatory attitudes and behaviors by instilling values of empathy, compassion, and acceptance. The article also discusses the importance of interfaith dialogue and collaboration in fostering understanding and breaking down barriers. Furthermore, it explores strategies for integrating Christian religious education within the Indonesian education system to address discrimination effectively. By nurturing a spirit of inclusivity and fostering respect for diversity, Christian religious education can play a vital role in creating a more harmonious and equitable society in Indonesia.   Artikel ini mengkaji peran pendidikan agama Kristen dalam memerangi diskriminasi dalam masyarakat Indonesia yang majemuk. Ini mengeksplorasi tantangan yang ditimbulkan oleh diskriminasi berdasarkan faktor-faktor seperti etnis, agama, dan status sosial-ekonomi, dan menyoroti potensi pendidikan agama Kristen untuk mempromosikan toleransi, rasa hormat, dan inklusivitas. Studi ini menyelidiki prinsip dan ajaran agama Kristen yang menekankan kesetaraan, keadilan, dan cinta sesama. Ini menganalisis bagaimana pendidikan agama Kristen dapat berkontribusi membongkar sikap dan perilaku diskriminatif dengan menanamkan nilai-nilai empati, kasih sayang, dan penerimaan. Artikel ini juga membahas pentingnya dialog dan kolaborasi antar agama dalam menumbuhkan pemahaman dan meruntuhkan sekat-sekat. Selain itu, bab ini mengeksplorasi strategi untuk mengintegrasikan pendidikan agama Kristen ke dalam sistem pendidikan Indonesia untuk mengatasi diskriminasi secara efektif. Dengan memupuk semangat inklusivitas dan menumbuhkan rasa hormat terhadap keberagaman, pendidikan agama Kristen dapat berperan penting dalam mewujudkan masyarakat yang lebih harmonis dan berkeadilan di Indonesia.